2016
DOI: 10.1002/2015ja021578
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind plasma entry observed by cluster in the high‐latitude magnetospheric lobes

Abstract: Using the Cluster data during the period from January to April between 2001 and 2006, we find an observation of solar wind entry due to magnetic reconnection occurred in the terrestrial high‐latitude magnetospheric lobes, tailward of the cusps under northward interplanetary magnetic field (IMF). Occurrence rate of solar wind entry events in this study is of the same order as that for the Cluster orbital interval from August to October between the years of 2002 and 2004 as reported by Shi et al. (2013). In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…During the subsequent time interval from 11:15 UT to 11:20 UT, the ARTEMIS probes encountered tailward high-speed flows accompanied by an increase in B X and an increase in total magnetic field strength from ∼0 nT to ∼40 nT, indicating that the probes have moved to the lobe region (Baumjohann et al, 1990;Pan et al, 2015Pan et al, , 2016Shang et al, 2014;Wei et al, 2014;. The plasma density in the lobe region is shown to have increased during this interval (compared to the interval shown prior to shock arrival, reaching 1 cm −3 ), presumably due to compression of the geotail plasma following the shock (Gou et al, 2016).…”
Section: Observationsmentioning
confidence: 85%
“…During the subsequent time interval from 11:15 UT to 11:20 UT, the ARTEMIS probes encountered tailward high-speed flows accompanied by an increase in B X and an increase in total magnetic field strength from ∼0 nT to ∼40 nT, indicating that the probes have moved to the lobe region (Baumjohann et al, 1990;Pan et al, 2015Pan et al, , 2016Shang et al, 2014;Wei et al, 2014;. The plasma density in the lobe region is shown to have increased during this interval (compared to the interval shown prior to shock arrival, reaching 1 cm −3 ), presumably due to compression of the geotail plasma following the shock (Gou et al, 2016).…”
Section: Observationsmentioning
confidence: 85%
“…During the subsequent time interval from 11:15 UT to 11:20 UT, the ARTEMIS probes encountered tailward high‐speed flows accompanied by an increase in B X and an increase in total magnetic field strength from ∼0 nT to ∼40 nT, indicating that the probes have moved to the lobe region (Baumjohann et al, ; Pan et al, , ; Shang et al, ; Wei et al, ; Yao et al, ). The plasma density in the lobe region is shown to have increased during this interval (compared to the interval shown prior to shock arrival, reaching 1 cm −3 ), presumably due to compression of the geotail plasma following the shock (Gou et al, ).…”
Section: Observationsmentioning
confidence: 88%
“…Several subsequent studies have investigated this phenomenon further. Some have adopted the interpretation of direct solar wind entry proposed by Shi et al (2013): Mailyan et al (2015) reported a conjunction between plasma populations of the type observed by Shi et al (2013) and a transpolar arc, interpreted in the framework of direct solar wind entry, implicitly placing the transpolar arc on open magnetic field lines, and Gou et al (2016) performed a statistical analysis, arguing that observed dependencies could be explained by IMF control of the high latitude reconnection process. Others have sided with a closed field line topology formed by magnetotail reconnection: argued that if transpolar arcs are formed by magnetotail reconnection, then an observed interaction between a transpolar arc and the cusp spot (Frey et al 2002) indicated that the high latitude reconnection process (indicated by the presence of the cusp spot) was actually opening the closed magnetic flux associated with the transpolar arc.…”
Section: Source Of Polar Cap Arc Plasmasmentioning
confidence: 99%